2011
DOI: 10.22358/jafs/66154/2011
|View full text |Cite
|
Sign up to set email alerts
|

Net nutrient flux in visceral tissues of goats fed diets based on maize or wheat

Abstract: The objective of this study was to investigate the effects of dietary starch sources on the net portaldrained viscera (PDV) flux of metabolites in goats fed diets based on maize and wheat, respectively. Eight 8-month-old Liuyang Black wether goats, with catheters surgically in the mesenteric vein, the portal vein and the carotid artery, were assigned to one of two diets for determination of net nutrient flux across the PDV. There were no differences (P>0.05) in plasma concentrations of glucose and ammonia-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We found that the goats fed the diet based on maize was associated with higher net fluxes of lysine, methionine and valine across the portal drained viscera (PDV), and lower urea-N concentration in the portal vein and net PDV flux of ammonia-N when compared with the goats fed the diet based wheat (Sun et al, 2011). On the basis of the above-mentioned study, the present study was carried out to investigate the growth performance and meat quality of goats fed the diets based on maize and wheat.…”
Section: Introductionmentioning
confidence: 95%
“…We found that the goats fed the diet based on maize was associated with higher net fluxes of lysine, methionine and valine across the portal drained viscera (PDV), and lower urea-N concentration in the portal vein and net PDV flux of ammonia-N when compared with the goats fed the diet based wheat (Sun et al, 2011). On the basis of the above-mentioned study, the present study was carried out to investigate the growth performance and meat quality of goats fed the diets based on maize and wheat.…”
Section: Introductionmentioning
confidence: 95%